2009
DOI: 10.1108/02686900910975387
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance, disclosure and foreign share ownership on the Ghana Stock Exchange

Abstract: PurposeThe purpose of this paper is to examine the interaction between corporate disclosure and foreign share ownership on the Ghana Stock Exchange (GSE).Design/methodology/approachThe paper follows the trinary procedure of Aksu and Kosedag and uses the Standard & Poor's transparency and disclosure items in the construction of the disclosure index. Therefore, the paper adopts a panel data analysis covering a period from 2002 to 2007 using the seemingly unrelated regression approach.FindingsThe results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 42 publications
3
58
2
1
Order By: Relevance
“…Due to the geographical barriers, foreign investors are likely to face a higher level of information asymmetry compared with their domestic counterparts (Oxelheim & Randoy, 2003). Accordingly, foreign investors tend to invest more in firms that disclose more information (Mangena & Tauringana, 2007;Bokpin & Isshaq, 2009). To reduce information asymmetry between foreign and domestic investors, firms are inclined to provide more information (Mangena & Tauringana, 2007).…”
Section: Foreign Ownershipmentioning
confidence: 99%
“…Due to the geographical barriers, foreign investors are likely to face a higher level of information asymmetry compared with their domestic counterparts (Oxelheim & Randoy, 2003). Accordingly, foreign investors tend to invest more in firms that disclose more information (Mangena & Tauringana, 2007;Bokpin & Isshaq, 2009). To reduce information asymmetry between foreign and domestic investors, firms are inclined to provide more information (Mangena & Tauringana, 2007).…”
Section: Foreign Ownershipmentioning
confidence: 99%
“…A number of studies have been undertaken about the relationship between corporate governance and foreign ownership (Bokpin & Isshaq, 2009;Leuz at al. 2009;Hossain, 2007;Mangena & Tauringana, 2007;Tsamenyi et al, 2007;Chevalier et al, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Ghana, Bokpin & Isshaq (2009) investigated the impact of transparency and corporate governance on foreign share ownership for a sample of listed firms on the Ghana stock exchange (GSE). They found that when foreign investors make their investment decisions they consider corporate governance and disclosure practices employed in the listed firms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the context of a previous study on foreign ownership, Isshaq (2009) andBokpinet al (2015) studied the effect of transparency and corporate governance on foreign share ownership, and found that decisions of foreign investors are based on corporate governance and disclosure norms of listed firms. It has also been revealed that foreign investors steer clear of investment in companies that lack a corporate governance structure and which have ineffective disclosure practices since disclosure and transparency are important for foreign investors (Mangena&Tauringana, 2007;Al-arussi, Selamat&Hanefah, 2009).…”
Section: Asian Journal Of Finance and Accountingmentioning
confidence: 99%